Physical Training Methods to Improve the Physical Condition Components of Elite Taekwondo Athletes in The Kyorugi Category: A Systematic Review - Fahmy Fachrezzy; Uzizatun Maslikah; Iwan Hermawan; Gatot Jariono; Haris Nugroho; Syahruddin (OVS LLC, 2024)
Objectives. The study aimed to provide a systematic review of physical training methods to improve the physical condition components of elite taekwondo athletes in the kyorugi category. Materials and methods. An extensive literature assessment of earlier research was carried out. The objective was to examine articles published between 2020 and 2024 that describe strategies for improving the physical condition component of taekwondo athletes. The electronic search was conducted using Google Scholar, PubMed, Web of Science, and Scopus. The articles that addressed methods for enhancing physical condition through exercise were compiled. Results.  Sixty publications used training approaches to enhance the physical condition component of elite taekwondo athletes in the kyorugi category. Based on the physical state that is assessed and improved, items are categorized. Among the physical training methods that can be applied in the Taekwondo category of kyorugi are plyometric training, circuit training methods, speed, agility, and quickness (SAQ) training; strength training, endurance training, flexibility training, reaction training, power training, coordination training, balance training, resistance training, and functional training. Conclusions. After thorough analysis, several training techniques have been shown to be effective in enhancing the physical attributes of elite taekwondo athletes in the kyorugi category. These attributes include flexibility, response, strength, power, coordination, agility, speed, balance, and VO₂max.